The Colour of Blood - Moore B. Brian (London, Flamingo, 1994)
Somewhere in an unnamed Eastern bloc country, someone is out to silence Cardinal Bern. Is it the Secret Police, or is it fanatical Catholic activists who believe that Bern, by keeping the peace between Church and State, has finally compromised himself too far? Abducted by sinister, anonymous men. Bern is spirited away to a 'safe house'. Evading his unknown captors, and no longer sure of whom he can trust. Bern realizes that he alone can avert the revolution which threatens to tear his country apart... With a new exclusive essay by John Watshю.